The legacy imprint of apprenticeship trajectories under conditions of segregation and Apartheid in South Africa - Gamble, Jeanne [Verfasser] (My University, 2021)
"In many countries, the contours of skills formation systems are traced back to early struggles over control of apprenticeship. This paper uses a curriculum lens to examine two distinctive policy moments in the history of formal apprenticeships in South Africa and to trace the legacy imprint of direct and indirect race-based exclusion as well as the imprint of educational deprivation in social class terms. The policy trajectory shows how an apprenticeship curriculum that had to cater for White working-class youth with low educational credentials led to a steady erosion of the formal knowledge component of the curriculum in favour of practical workplace experience. Alongside race-based exclusion, a neglect of science-based knowledge emerges as a lasting curriculum legacy of apprenticeship trajectories under conditions of segregation, Apartheid and their colonial precursors." (Author's abstract ; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; T 1.2 Historische Berufsbildungsforschung; I 2.3.1 Afrika; 370; Berufsausbildung; Berufsbildungssystem; Deprivation; Historische Entwicklung; Lehrplan; Rassismus; Kolonialismus; Südafrika